Parabolic relationship between SMAD3 expression level and the reprogramming efficiency of goat induced mammary epithelial cells - Wu, Yulian; Zhang, Dandan; Ye, Sheng; Liu, Quanhui; Huang, Ben (Frontiers in Cell and Developmental Biology, 2022)
Mammary epithelial cells are the only cells of mammary glands with lactation capacity. They are closely related to mammary development and milk yield. Our earlier studies showed that the transformation of goat fibroblasts into induced mammary epithelial cells (iMECs) was closely correlated with SMAD3 overexpression. Therefore, we further explored the role of SMAD3 on iMECs reprogramming in this study. The SMAD3 gene was overexpressed in goat ear fibroblasts using the tetracycline-induced expression method. The outcomes demonstrated that goat ear fibroblasts can be converted into iMECs by overexpressing the SMAD3 gene. In contrast, it was discovered that SMAD3 downregulation by RNA interference significantly decrease the reprogramming efficiency of iMECs. These results show that SMAD3 plays a key regulatory role in the reprogramming of iMECs. Surprisingly, we also found a parabolic relationship between SMAD3 expression level and iMECs reprogramming efficiency, and that the reprogramming efficiency was maximum when the addition of doxycycline concentration was 5 μg/mL. In light of this, our findings may offer new perspectives on the regulatory mechanism governing mammary epithelial cell fate in goats as well as a fresh approach to studying mammary development and differentiation in vitro.